Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the expression [tex]\( \left(\frac{8^{-5}}{2^{-2}}\right)^{-4} \)[/tex], we need to simplify it step by step.
1. Begin by simplifying the expression inside the parentheses: [tex]\(\frac{8^{-5}}{2^{-2}}\)[/tex].
2. Use the property of exponents that [tex]\(\frac{a^m}{b^n} = a^m \cdot b^{-n}\)[/tex]:
[tex]\[ \frac{8^{-5}}{2^{-2}} = 8^{-5} \cdot 2^2 \][/tex]
3. Note that [tex]\(8\)[/tex] can be written as [tex]\(2^3\)[/tex]:
[tex]\[ 8 = 2^3 \][/tex]
4. Thus, [tex]\(8^{-5}\)[/tex] can be rewritten using the base 2:
[tex]\[ 8^{-5} = (2^3)^{-5} = 2^{3 \cdot (-5)} = 2^{-15} \][/tex]
5. Substitute [tex]\(2^{-15}\)[/tex] back into the expression:
[tex]\[ 2^{-15} \cdot 2^2 \][/tex]
6. Combine the exponents using the property [tex]\(a^m \cdot a^n = a^{m+n}\)[/tex]:
[tex]\[ 2^{-15 + 2} = 2^{-13} \][/tex]
7. Now, the original expression inside the parentheses is simplified to:
[tex]\[ (2^{-13})^{-4} \][/tex]
8. Apply the power-of-a-power property [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ (2^{-13})^{-4} = 2^{-13 \cdot -4} = 2^{52} \][/tex]
So, the equivalent expression for [tex]\( \left(\frac{8^{-5}}{2^{-2}}\right)^{-4} \)[/tex] is:
[tex]\[ 2^{52} \][/tex]
Finally, let's compare this result with the choices provided:
(A) [tex]\( \frac{1}{8 \cdot 2^2} \)[/tex]
(B) [tex]\( \frac{2^6}{8^9} \)[/tex]
(C) [tex]\( \frac{8^{20}}{2^8} \)[/tex]
To determine which choice matches [tex]\(2^{52}\)[/tex], let's simplify each option:
- (A) [tex]\( \frac{1}{8 \cdot 2^2} \)[/tex]
[tex]\[ 8 = 2^3 \Rightarrow 8 \cdot 2^2 = 2^3 \cdot 2^2 = 2^{5} \][/tex]
[tex]\[ \frac{1}{2^{5}} \neq 2^{52} \][/tex]
- (B) [tex]\( \frac{2^6}{8^9} \)[/tex]
[tex]\[ 8 = 2^3 \Rightarrow 8^9 = (2^3)^9 = 2^{27} \][/tex]
[tex]\[ \frac{2^6}{2^{27}} = 2^{6-27} = 2^{-21} \neq 2^{52} \][/tex]
- (C) [tex]\( \frac{8^{20}}{2^8} \)[/tex]
[tex]\[ 8 = 2^3 \Rightarrow 8^{20} = (2^3)^{20} = 2^{60} \][/tex]
[tex]\[ \frac{2^{60}}{2^{8}} = 2^{60-8} = 2^{52} \][/tex]
This matches our original result of [tex]\(2^{52}\)[/tex].
Therefore, the correct choice is:
(C) [tex]\(\frac{8^{20}}{2^8}\)[/tex]
1. Begin by simplifying the expression inside the parentheses: [tex]\(\frac{8^{-5}}{2^{-2}}\)[/tex].
2. Use the property of exponents that [tex]\(\frac{a^m}{b^n} = a^m \cdot b^{-n}\)[/tex]:
[tex]\[ \frac{8^{-5}}{2^{-2}} = 8^{-5} \cdot 2^2 \][/tex]
3. Note that [tex]\(8\)[/tex] can be written as [tex]\(2^3\)[/tex]:
[tex]\[ 8 = 2^3 \][/tex]
4. Thus, [tex]\(8^{-5}\)[/tex] can be rewritten using the base 2:
[tex]\[ 8^{-5} = (2^3)^{-5} = 2^{3 \cdot (-5)} = 2^{-15} \][/tex]
5. Substitute [tex]\(2^{-15}\)[/tex] back into the expression:
[tex]\[ 2^{-15} \cdot 2^2 \][/tex]
6. Combine the exponents using the property [tex]\(a^m \cdot a^n = a^{m+n}\)[/tex]:
[tex]\[ 2^{-15 + 2} = 2^{-13} \][/tex]
7. Now, the original expression inside the parentheses is simplified to:
[tex]\[ (2^{-13})^{-4} \][/tex]
8. Apply the power-of-a-power property [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ (2^{-13})^{-4} = 2^{-13 \cdot -4} = 2^{52} \][/tex]
So, the equivalent expression for [tex]\( \left(\frac{8^{-5}}{2^{-2}}\right)^{-4} \)[/tex] is:
[tex]\[ 2^{52} \][/tex]
Finally, let's compare this result with the choices provided:
(A) [tex]\( \frac{1}{8 \cdot 2^2} \)[/tex]
(B) [tex]\( \frac{2^6}{8^9} \)[/tex]
(C) [tex]\( \frac{8^{20}}{2^8} \)[/tex]
To determine which choice matches [tex]\(2^{52}\)[/tex], let's simplify each option:
- (A) [tex]\( \frac{1}{8 \cdot 2^2} \)[/tex]
[tex]\[ 8 = 2^3 \Rightarrow 8 \cdot 2^2 = 2^3 \cdot 2^2 = 2^{5} \][/tex]
[tex]\[ \frac{1}{2^{5}} \neq 2^{52} \][/tex]
- (B) [tex]\( \frac{2^6}{8^9} \)[/tex]
[tex]\[ 8 = 2^3 \Rightarrow 8^9 = (2^3)^9 = 2^{27} \][/tex]
[tex]\[ \frac{2^6}{2^{27}} = 2^{6-27} = 2^{-21} \neq 2^{52} \][/tex]
- (C) [tex]\( \frac{8^{20}}{2^8} \)[/tex]
[tex]\[ 8 = 2^3 \Rightarrow 8^{20} = (2^3)^{20} = 2^{60} \][/tex]
[tex]\[ \frac{2^{60}}{2^{8}} = 2^{60-8} = 2^{52} \][/tex]
This matches our original result of [tex]\(2^{52}\)[/tex].
Therefore, the correct choice is:
(C) [tex]\(\frac{8^{20}}{2^8}\)[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.